تأثير الأداءات السياسية لإدارة الرئيس الأمريكي دولاندترامب عمى القضية الفلسطينية ( 2017 - 2021 - عبدالله عبد الجواد زمطأ (جامعة المسيلة, 2025)
This study examines the Trump administration’s policy toward the Palestinian cause during the period 2017–2021, which marked a clear shift from traditional U.S. mediation to overt support for Israel. It reviews key actions such as moving the U.S. embassy to Jerusalem, proposing the "Deal of the Century," cutting UNRWA funding, recognizing Israeli settlements and the Golan Heights, and sponsoring normalization agreements. The study highlights the impact of these policies on Palestinian governance, as well as the economic and humanitarian conditions in the occupied territories, in addition to their regional and international implications. It concludes that these policies marginalized the Palestinian cause and weakened prospects for a just solution. The study recommends national unity, activating legal and diplomatic channels, and resisting unconditional normalization.
Keywords: Trump policy; Palestinian cause; Deal of the Century; embassy relocation; UNRWA; settlements; Abraham Accords; normalization